2020
DOI: 10.1039/c9en01017c
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the toxicity of engineered nanomaterials to Tetrahymena thermophila in freshwater: the critical role of organic matter

Abstract: Organic matter could highly affect the bioavailability of nanomaterials which depends on the composition and conformation of the organic matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…However, Yang et al (Yang et al 2013) reported that the addition of HA decreased the concentration of Ti associated with fish, and increased the toxicity of TiO 2 NMs. These results were similar to the findings of Liang et al (Liang et al 2020a). The differences among toxicity mechanisms of NMs may be responsible for this finding; however, more specific work is required to understand the difference between the effects of NMs with an eco-corona and those without an eco-corona.…”
Section: Mechanisms By Which Nom Influences the Toxicity Of Nms By Aq...supporting
confidence: 93%
See 4 more Smart Citations
“…However, Yang et al (Yang et al 2013) reported that the addition of HA decreased the concentration of Ti associated with fish, and increased the toxicity of TiO 2 NMs. These results were similar to the findings of Liang et al (Liang et al 2020a). The differences among toxicity mechanisms of NMs may be responsible for this finding; however, more specific work is required to understand the difference between the effects of NMs with an eco-corona and those without an eco-corona.…”
Section: Mechanisms By Which Nom Influences the Toxicity Of Nms By Aq...supporting
confidence: 93%
“…Only a few studies have removed free organic matter through centrifugation to determine the influence of an eco-corona on the biological effects of NMs (Lin et al 2012). The formation of an eco-corona was proven by the change of zeta potential in most studies, whereas the decrease in the concentration of organic matter in the solution as well as shifts in the infrared spectrum and SEM were also used to confirm the formation of an ecocorona (Liang et al 2020a;Zhao et al 2019). As for the proteins, several studies used sodium dodecyl sulfate polyacrylamide gel electrophoresis technology (SDS-PAGE) to separate and detect the coated proteins (Fadare et al 2020).…”
Section: Dual Role Of An Eco-corona In the Accumulation/ Toxicity Beh...mentioning
confidence: 99%
See 3 more Smart Citations